Optimisasi Perencanaan Produksi Pupuk Menggunakan Firefly Algorithm - Dinita Rahmalia; Awawin Mustana Rohmah (Mathematics Department, Faculty of Science and Technology, UIN Sunan Ampel Surabaya, 2018)
In Indonesia, there are many farmers as a livelihood because of fertile soil for agriculture and the demand for food. Production planning is the important part of managing cost spent by the company. In production planning, there are many constraints which have to be satisfied such as the number of productions, the number of workers, and the number of inventory. In previous research, constrained optimizations have been solved by exact method or heuristic method. In this research, production planning optimization will be solved by Firefly Algorithm (FA). FA works as a behavior of Firefly. One of firefly behavior used is less bright firefly will move toward brighter firefly. The simulation results show that FA method can find an approaching optimal solution of production planning like production cost, worker cost, and inventory holding cost satisfying the constraints of the number of productions, workers, and inventory.